Biocontrol of Fusarium oxysporum f. sp. cepae on Indonesian Local Garlic Plants (Lumbu Hijau) Using a Consortium of Bacillus amyloliquefaciens B1 and Arbuscular Mycorrhizal Fungi - Fibrianti Shinta Dewi; Rifani Rusiana Dewi; Abdul Latief Abadi; Adi Setiawan; Luqman Qurata Aini; Muhammad Akhid Syib’li (Mycobiology)
Garlic (Allium sativum) is an indispensable ingredient for enriching and diversifying Indonesian cuisine taste. Indonesian people always use garlic for their daily dishes and any traditional foods. Due to its widespread culinary use, its availability in the market become critical. The main challenge to consistently growing this garlic is Fusarium oxysporum f. sp. cepae, which wilts Allium plants. The application of arbuscular mycorrhiza fungi (AMF) + Bacillus amyloliquefaciens B1 on local garlic varieties named Lumbu Hijau could effectively control F. oxysporum through in vitro and in vivo experiments. In the in vitro test, B. amyloliquefaciens B1 successfully suppressed the growth of F. oxysporum up to 53.41%. The consortium application in the greenhouse reduced disease incidence by up to 39.17%, and the efficacy of this biocontrol reached 84%. In addition, this approach also positively influenced plant growth, such as plant height, total wet shoot and root weight, and also tuber weight. As such, it is essential to use this consortium of microorganisms in field research and carry out a comprehensive investigation to identify any possible phenomena that may arise in the rhizosphere after application.